Inclusion Complex of Isoliquiritigenin With Sulfobutyl Ether-β-Cyclodextrin: Preparation, Characterization, Inclusion Mode, Solubilization, and Stability - Wu, Xiaozheng; Li, Jiamin; Hu, Chunmei; Zheng, Yingying; Zhang, Yufei; Li, Jianping; Li, Mengyue; Xiao, Di; Lu, Li; Huang, Yuechang; Zhang, Xingmin; Li, Chen (Frontiers in Chemistry, 2022)
Isoliquiritigenin (ISL) possesses a wide variety of pharmacological properties, however, its poor solubility and oral bioavailability poses a significant barrier to its application. In present studies, the ISL inclusion complex was prepared with sulfobutyl ether-β-cyclodextrin (SBE-β-CD). The physicochemical characterizations of ISL-SBE-β-CD were performed with Fourier transform infrared (FT-IR) spectroscopy and X-ray powder diffraction (XRD). Phase solubility study suggested a 1:1 formation of ISL-SBE-β-CD complexes. The water solubility of ISL rose from 13.6 μM to 4.05 mM by the inclusion with SBE-β-CD. The antioxidant activities (IC50) of ISL-SBE-β-CD reached to 42.2 μg/mL, which was significantly lower than that of ISL (60.5 μg/mL). It’s stability in biological environments was also enhanced.